2017
DOI: 10.5797/jnet.oa.2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Clopidogrel Hyper-response after Neuroendovascular Therapy Associated with Hemorrhagic Complications

Abstract: Objective: Changes in the VerifyNow (Accumetrics, San Diego, CA, USA) assay results before and after neuroendovascular therapy and complications were evaluated. Methods:Of the 124 neuroendovascular procedures at our hospital between June 2014 and June 2015, 15 patients received elective treatment with dual-antiplatelet therapy (DAPT) consisting of aspirin at 100 mg/day and clopidogrel at 75 mg/day continued from at least 7 days before the procedure to the postprocedural period. Of these patients, those who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The prognosis, particularly in CAS cases, tends to be unfavorable. The perioperative administration of multiple antiplatelet agents and anticoagulants may exacerbate post-bleeding outcomes in CAS procedures, as has been reported with increased hemorrhagic complications due to clopidogrel hyper-response [ 4 ]. Concerning the timing of bleeding, occurrences post-CEA typically present later, suggesting a potential association with hyperperfusion syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis, particularly in CAS cases, tends to be unfavorable. The perioperative administration of multiple antiplatelet agents and anticoagulants may exacerbate post-bleeding outcomes in CAS procedures, as has been reported with increased hemorrhagic complications due to clopidogrel hyper-response [ 4 ]. Concerning the timing of bleeding, occurrences post-CEA typically present later, suggesting a potential association with hyperperfusion syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment and prognosis, the patient in this report received strict blood pressure management, leading to favorable outcomes. Previous reports have documented cases of transient neurological deficits even in the presence of cortical SAH [ 4 ], underscoring the necessity for blood pressure control as in the case of cerebral hyperperfusion syndrome when hemorrhage is detected.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Delgado Almandoz et al, 23) 59% of PRU normo-responders were later converted to hyper-responders. Furthermore, Endo et al 24) showed that continuation of dual-antiplatelet therapy consisting of aspirin and clopidogrel induced delayed clopidogrel hyper-response and was associated with postoperative hemorrhagic complications. Therefore, excessive inhibition should be avoided to prevent hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%